Heat Resistance of Listeria monocytogenes in Dairy Matrices Involved in Mozzarella di Bufala Campana PDO Cheese - Ricci, Annalisa; Alinovi, Marcello; Martelli, Francesco; Bernini, Valentina; Garofalo, Alessandro; Perna, Giampiero; Neviani, Erasmo; Mucchetti, Germano (Frontiers in Microbiology, 2021)
The presence of Listeria monocytogenes in Mozzarella di Bufala Campana PDO cheeses may depends on curd stretching conditions and post contaminations before packaging. To break cross-contamination cycle, thermal treatment of water, brines and covering liquid may become necessary. The present study aimed to improve knowledge about L. monocytogenes thermal resistance focusing on the influence of matrices in order to optimize efficacy and sustainability of the processes. Moreover, the role that cheese curd stretching plays in L. monocytogenes inactivation was discussed. The 12 tested strains showed a very heterogeneous heath resistance, ranging from 7 to less than 1 Log CFU/mL reduction after 8 minutes at 60°C. D-values (decimal reduction times) and z-values (thermal resistance constant) calculated for the most heath resistant strain among 60 and 70°C were highly affected by the matrix and, in particular, heath resistance noticeably increased in drained cheese curd. As cheese curd stretching is not an isothermal process, to simulate the overall lethal effect of an industrial process a model has been built. The lethal effect of the process was estimated around 4 log10 reductions. The data provided may be useful for fresh pasta filata cheese processors in determining appropriate times and temperatures for producing safe cheeses.